Development of geo-polymer based Ductile Fibre Reinforced Cementitious Composites (DFRCC) - Ahmed, Shaikh; Hossain, Mokbul; Lu, Yee Yong (CRC Press/Balkema, 2012)
This paper presents the development of geopolymer based Ductile Fibre Reinforced Cementitious Composites (DRFCC) containing steel and two types of polyvinyl alcohol (PVA) fibres. The fibres are used in mono form in the development of both cement based and geo-polymer based DFRCCs. The effects of two different sand sizes (1.18 mm, and 0.6 mm) and sand/binder ratios (0.5 and 0.75) on the deflection hardening and multiple cracking behaviour of both types of DFRCC are also evaluated. Results revel that the deflection hardening and multiple cracking behaviour can be achieved in geo-polymer based DFRCC similar to that observed in cement based system. For a given fibre type, sand size and sand content, comparable Modulus Of Rupture (MOR) and the deflection at peak load are observed in both cement and geo-polymer based composites. The newly developed geo-polymer based DFRCC exhibit a significant benefit over cement based system as the former one is green in terms of no cement use.